Effectiveness of Teaching Economics in Higher Secondary School Level, Nepal - Khadka, Chakra Bahadur (Economic Journal of Development Issues, 2018)
Teaching economics to students in a clear and unbiased manner supports beginner students, master the essential principles of understanding the economizing problem, specific economic issues, help the student to understand and apply economics in a precise and empirical manner on economic issues and promote a lasting student interest in issue of economics.The objective of this paper is to analyze the effectiveness of teaching economics in higher secondary school level. Two hundred four teachers and equal students’ number have been selected for questionnaire survey. The survey data were collected from different training centers of the training and workshop interval. Psychometric scale, was designed for data collection. For the data analysis, SEM is used, including simultaneously complete tests of model fit, together with simultaneously overall tests of model fit, specific parameter estimates, compare simultaneously, OLS coefficients, Means and Variances. The finding is based on the assumption that is; default model is correct, the probability of getting a discrepancy as significant as 73.59 is 0.00 of students' understanding of economics in their classroom. Maximum likelihood estimates at all the parameter estimates are highly significant. If EFET positive change by 1, T_EFET_2 also positively change by 0.88. The regression weights to estimate, 0.88, has a standard error of about 0.06. Dividing the regression weight estimate by the estimate of its standard error gives z = 0.88/0.06 = 14.91. The variables of student understanding are significantly different from 0 except S_QOAT_4. As ATME positive changes by 1, S_ATME_2 also positively change 0.57. The regression weights to estimate, 0.57, has a standard error of about 0.04. Students they agreed with 8A and 9A statement. This is recommended that teach the teachers as a workshop style and training in improving economics instruction in Higher Secondary Schools Level. The experimental program helps teachers to gain an understanding of economic concepts and improve pedagogy. Improved classroom environment, the latest text materials might be the encouraging to economics subject to the student. Economic Journal of Development Issues Vol. 21 & 22 No. 1-2 (2016) Combined Issue, Page:99-126